The Role of Intrinsic Motivation in Mediating Transformational Leadership Style and Islamic Work Ethics on Sustainable Human Resource Performance - Lutfiyyah, Yumna; Azzuhri, Misbahuddin (Jurnal Kewirausahaan dan Inovasi, 2025)
This explanatory quantitative study aims to examine how transformational leadership style and Islamic work ethics influence sustainable human resource performance at SMP IT Al Mumtaz in Pontianak, with intrinsic motivation as a moderating variable. This census study included all 50 employees as the sample. Data collected through questionnaires were analyzed using multiple linear regression in IBM SPSS 30.0 for Windows. The study found that transformational leadership style, Islamic work ethics, and intrinsic motivation significantly positively affect sustainable human resource performance. Furthermore, intrinsic motivation mediates the relationship between transformational leadership style and sustainable human resource performance but does not mediate the effect of Islamic work ethics on sustainable human resource performance.